POTENSI HERBA & REMPAH SEBAGAI TANAMAN OBAT KELUARGA - GH, Muliana; Rasyid, Magfirah; Hasanah, Ummul (Universitas Sulawesi Barat, 2023)
This research is a literature review that aims to explore the potential of spices and herbs in their use as family medicinal plants, with a focus on collecting data on plant ingredients and the use of plants as traditional medicine. In an effort to find traditional medicines that are safe, effective and affordable for family health problems, traditional medicines derived from plants are a treatment approach that is based on natural resources. This article outlines some of the spices and herbs that have long been used in traditional medicine, and highlights the latest scientific research showing the effectiveness and safety of some medicinal plants. Some of the spices and herbs discussed in this article include ginger, turmeric, galangal, bitter, kencur, temulawak, cocor duck, betel, garlic, pagagan, meniran, lime and binahong. Further research is needed to evaluate and validate the potency of spices and herbs in their use as family medicinal plants. Keywords: Spices, herbs, medicinal plants